(3TQM Ce GdHQGgjfs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg Pj GdLdGd hGdEcQGe abO SCdfj HYVef CYJbO UdGMg Cf CTQM GdYbjOI GdeSeGI HCe GdHQGgjf JCdja GdEeGe CHj YHO Gddg eMeO Hf jhSa GdSfhSj GdMSfj GdeZQHj s
(3BNQgG (B:s
(3aGFOI (B: (3ojQhi Cf GdeQGFcI bGdJ(B: (3jGQH dh Cf GdSeGA hGdCQV Mjf CeQJgeG YUjGcG eG cfJ UGfYG HgeG ? bGd (B: (3cfJ BeQ OGHI ef OhGHj aJHdYgeG , bGdhG(B: (3jGQH hCjf Jdc GdOGHI? bGd (B: (3aj eQL ef eQhLj hbY GdaQGZs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds